Melatonin inhibits testosterone secretion by acting at hypothalamo-pituitary-gonadal axis in the rat - Yilmaz, B; Kutlu, S; Mogulkoç, R; Canpolat, S; Sandal, S; Tarakçi, B; Kelestimur, H (Maghira & Maas Publications, 2000)
OBJECTIVES: We have investigated the changes in serum luteinizing hormone (LH), follicle stimulating hormone (FSH) and testosterone levels together with testicular histology in both pinealectomized (PNX) and intact rats. MATERIAL and METHODS: Twenty-one animals were PNX and allowed to recover for two months. Group I was assigned as PNX, group II PNX+melatonin and group III PNX+Human Chorionic Gonadotropin (HCG). Rats in group IV were sham PNX (S-PNX). An intact group of animals was s.c. injected with melatonin (0.5 mg/kg/day), another group with a combination of melatonin+HCG (5000 IU/kg/day) for seven days. Controls received saline alone (1 ml/kg). At the end, all animals were decapitated and blood samples obtained. Serum LH and FSH levels were determined by Radioimmunoassay, testosterone values by Chemiluminescent Enzyme Immunoassay. Testicular tissue was collected and processed for light microscopy. RESULTS: Serum LH levels were increased following PNX, but no such increases were seen in testosterone. In the PNX+melatonin group, serum LH and testosterone values were found to be similar to those of S-PNX group. HCG supplementation to PNX rats resulted in significant decreases in LH (p<0.005), but increased testosterone levels (p<0.001). Melatonin administration to intact animals significantly decreased both LH and testosterone levels (p<0.01). Go-administration of HCG+melatonin resulted in significant decreases in LH (p<0.001) and increases in testosterone levels (p<0.01). Serum FSH values did not show significant changes among groups. Only HCG administration significantly reduced FSH levels (p<0.01). CONCLUSIONS: Our results suggest that melatonin inhibits testosterone secretion by acting at hypothalamo-pituitary axis. There is a functional relationship and feedback regulation between the pineal gland and the testes.
Keywords: pinealectomy; melatonin; LH; testosterone; FSH; HCG